1986
DOI: 10.1002/jlb.39.1.77
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Local Resident Pulmonary Alveolar Macrophage Proliferation to Population Renewal

Abstract: The local proliferative capacity of resident pulmonary alveolar macrophages (PAM) was determined in normal CD-1 (ICR) mice and mice made severely monocytopenic with strontium-89 (89Sr). Intravenous injection of 2 muCi/gm BW 89Sr rendered mice monocytopenic for a 1-month period. During this time, in addition to there being no change in the size of the PAM population, flash 3HTdR labeling studies showed that at any one instant about 8.8 X 10(3) of PAM in 88Sr-treated controls and 9.2 X 10(3) PAM in 89Sr-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…Various studies on the origin of the AM indicate that in normal animals, the population is maintained by local proliferation (3,4). This may occur in AM in situ (11 ) or in precursor cells in the interstitium (3,12), and several studies that indicate a local origin of AMs refer to pulmonary macrophage proliferation without distinguishing cellular location (13,14). In the present study, there was no reduction in AM in mice receiving radiation only, further supporting a local origin for these cells in monocyte-depleted animals.…”
Section: Discussionsupporting
confidence: 71%
“…Various studies on the origin of the AM indicate that in normal animals, the population is maintained by local proliferation (3,4). This may occur in AM in situ (11 ) or in precursor cells in the interstitium (3,12), and several studies that indicate a local origin of AMs refer to pulmonary macrophage proliferation without distinguishing cellular location (13,14). In the present study, there was no reduction in AM in mice receiving radiation only, further supporting a local origin for these cells in monocyte-depleted animals.…”
Section: Discussionsupporting
confidence: 71%
“…A reported selfrenewal capacity allows macrophages to survive for long periods. [45][46][47] Therefore, residing macrophages in the spleen may have selfrenewed to maintain the number of macrophages. In the present study, we examined only the number of macrophages and not their functions.…”
Section: Discussionmentioning
confidence: 99%
“…Subpopulations of AMs were identified in the lungs of normal rats [23][24][25], guineapigs [26], rabbits [27], and humans [3,5,28,29]. Several experimental studies have suggested that resident AM populations in the normal lung are maintained by local division of cells and that the influx of peripheral monocytes is not needed to sustain the AM population [6,30,31]. In contrast, BOWDEN and ADAMSON [7] postulated that under normal circumstances the predominant mechanism of macrophage production is direct passage of monocytes across the interstitium to the alveoli, and that only a smaller proportion of cells appears to arise after division of resident interstitial cells with subsequent migration to the alveoli.…”
Section: Discussionmentioning
confidence: 99%